Assessment of functional mobility and body mass index among patients with a total knee replacement: a retrospective study in Indian population - Yelamarthi, Nagendra Gowtham Rayudu; Yelavarthi, Raghu; Tati, Rajashekhar (International Journal of Research in Orthopaedics, 2019)
Background: Obesity is associated with an increased risk of osteoarthritis, and the incidence of obese patients requiring a total knee replacement (TKR) has increased in recent years. A high body mass index (BMI) may influence post‐TKR rehabilitation outcomes. The aim of the present study was to assess the effects of obesity on functional mobility outcomes following post‐TKR rehabilitation in Asian patients where BMI was not as high as those reported in similar studies performed other countries other than Asian. Methods: A total of 125 patients were categorized as normal weight (n=25), overweight (n=25), class I obese (n = 25), or class II/III obese (n=25 each). Patients were retrospectively followed up for 6 months after undergoing TKR followed by 2 months of active rehabilitation. Outcome measures were recorded at baseline and at the 2‐month and 6‐month follow-up assessments and included the Western Ontario and McMaster Universities Osteoarthritis Index and the following tests: functional reach, single‐leg stance, ten‐meter walk, timed up and go, chair rise, and stair climbing. Results: A 4×3 (group×time) repeated‐measures analysis of variance showed significant improvement in all of the outcome measures for all of the BMI groups at the 2‐month and 6‐month follow-up assessments (p<0.05 for all). No significant intergroup differences at the 2‐month and 6‐month follow-up assessments were observed for any of the mobility measures except the functional reach and single‐leg stance (p<0.05). Conclusions: Patients with class II/III obesity benefit from early post‐TKR outpatient rehabilitation and respond well. Also, the patients with lower BMIs showed significant improvements and patients with a high BMI might require additional balance-based exercises in their post-TKR rehabilitation protocols.